2013
DOI: 10.1080/19368623.2013.771114
|View full text |Cite
|
Sign up to set email alerts
|

Theory in Hospitality, Tourism, and Leisure Studies

Abstract: Abstract:The term "theory" is used with diverse meanings, resulting in miscommunication and misunderstanding. This article examines how "theory", as a word, is used in three leading journals in each of hospitality, tourism, and leisure studies fields over a 20-year period. Utilizing an iterative and comparative hierarchical coding, seven different forms of theory and trends in their usage by scholars over the 20 years are identified. Among the notable trends are: 1) A marked increase in the appearance of "theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…These limitations apart, the study sheds through its implications some much-needed light to the discussion of the nature and uses of tourism theory -a topic of growing concern and interest for tourism researchers (Smith et al, 2013). The findings reported here have no claims to generalisability.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…These limitations apart, the study sheds through its implications some much-needed light to the discussion of the nature and uses of tourism theory -a topic of growing concern and interest for tourism researchers (Smith et al, 2013). The findings reported here have no claims to generalisability.…”
Section: Discussionmentioning
confidence: 66%
“…As a result, many tourism journal editors expect submissions to be positioned in a theoretical context and demonstrate their contribution to theory (e.g. Franklin and Crang, 2001;Perdue et al, 2009;Xiao et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…in tourism and is likely to become a primary point of reference in tourism research." However, the terms "theory" and "theoretical contribution" are grossly misunderstood by research scholars, and are sometimes loosely defined (Smith et al, 2013). The number of journal editorials and articles discussing the nature of theory and what constitutes theoretical contribution testifies to the depth of academic debate on the topic (e.g., Corley and Gioia, 2011;Cortina, 2016;Crane et al, 2016;Smith et al, 2013;Nunkoo and Ramkissoon, 2012;Whetten, 1989).…”
Section: Part I: Foundations Of Tourism and Hospitality Researchmentioning
confidence: 99%
“…Tracy explained the importance of theory in advancing hospitality research, advocating its use by scholars. Likewise, Smith et al (2013) examined how "theory," as a word, is used in three leading journals in each of hospitality, tourism, and leisure studies fields over a 20-year period. The article concluded that researchers have succeeded only in developing mutually incomprehensible languages and worldviews, failing to reach a consensus on the true meaning of the term "theory."…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation